2009
DOI: 10.1073/pnas.0903200106
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cerebral β-amyloidosis: Intracerebral versus systemic Aβ inoculation

Abstract: Despite the importance of the aberrant polymerization of A␤ in the early pathogenic cascade of Alzheimer's disease, little is known about the induction of A␤ aggregation in vivo. Here we show that induction of cerebral ␤-amyloidosis can be achieved in many different brain areas of APP23 transgenic mice through the injection of dilute A␤-containing brain extracts. Once the amyloidogenic process has been exogenously induced, the nature of the induced A␤-deposition is determined by the brain region of the host. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
248
1
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 259 publications
(275 citation statements)
references
References 44 publications
(66 reference statements)
11
248
1
8
Order By: Relevance
“…Recently, it has been shown that inoculation of brain homogenates from aged Tg(APP23) mice into the brains of young Tg(APP23) mice resulted in the accelerated induction of Aβ deposition in proximity to the inoculation site (24,25). We asked whether this accelerated Aβ deposition also coincided with an increase in GFAP levels that could be monitored using our bigenic Tg(APP23:Gfap-luc) mice.…”
Section: Bli Of Accelerated Disease In Tg(app23:gfap-luc) Mice Inoculmentioning
confidence: 99%
“…Recently, it has been shown that inoculation of brain homogenates from aged Tg(APP23) mice into the brains of young Tg(APP23) mice resulted in the accelerated induction of Aβ deposition in proximity to the inoculation site (24,25). We asked whether this accelerated Aβ deposition also coincided with an increase in GFAP levels that could be monitored using our bigenic Tg(APP23:Gfap-luc) mice.…”
Section: Bli Of Accelerated Disease In Tg(app23:gfap-luc) Mice Inoculmentioning
confidence: 99%
“…Similarly, i.p. injections of brain extracts laden with Aβ aggregates into transgenic mice expressing the amyloid precursor protein also induced cerebral β-amyloidosis (49,50). Overall, our experience has been that using transgenic mice in exogenous seeding experiments greatly enhances the probability of transmitting pathogenic protein aggregation.…”
Section: Discussionmentioning
confidence: 77%
“…The ability of Ab and Tau to induce aggregation of endogenous proteins after intracerebral injections may suggest that a-syn could also display seeding capacity in vivo, even if this property has yet to be properly demonstrated. Finally, in contrast to oral, intravenous, intraocular, and intranasal inoculation of Ab-containing brain extracts, which do not lead to any detectable cerebral amyloidosis, 87 intraperitoneal injections of these extracts are able to induce Ab deposition in the brains of young transgenic APP mice after a 7-month incubation period. 88 These results suggest that transport of Ab from periphery to brain can occur and might be a first step in questioning the presumed noninfectious features of AD.…”
Section: Intercellular Transfer Of A-syn In Animal Modelsmentioning
confidence: 99%